2012
DOI: 10.3382/ps.2012-02339
|View full text |Cite
|
Sign up to set email alerts
|

Different combinations of probiotics improve the production performance, egg quality, and immune response of layer hens

Abstract: To evaluate the effects of different combinations of probiotics on performance, egg quality, and immune response of layer hens, a trial was carried out with 1,800 white feather layer hens of the Lohmann variety. The experiment was conducted by using a completely randomized design with 9 treatments, 4 replicates, and 50 hens in each replicate. Compared with the control group, group F, which added a composition of heat-inactivated Lactobacillus salivarius(CB) and Bacillus subtilis to the diets of layer hens, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 20 publications
4
46
1
1
Order By: Relevance
“…did not result in an increase in FCR (Ginzberg et al, 2000;Bozkurt et al, 2012). This variation may be attributed to the age or strain (or both) of birds used in the experiment and also the type of seaweed used and inclu- sion rates, as well as the differences in the experimental conditions such as temperature and humidity (Geier et al, 2009;zhang et al, 2012). The increase in egg and yolk weight with 1% level of seaweeds (1% CC and SG) might be attributed to higher yolk protein synthesis and an increase in water and mineral availability (Novak et al, 2004) and greater retention of feed in the gastrointestinal tract and thus a better ileal digestibility of the feed (Piray et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…did not result in an increase in FCR (Ginzberg et al, 2000;Bozkurt et al, 2012). This variation may be attributed to the age or strain (or both) of birds used in the experiment and also the type of seaweed used and inclu- sion rates, as well as the differences in the experimental conditions such as temperature and humidity (Geier et al, 2009;zhang et al, 2012). The increase in egg and yolk weight with 1% level of seaweeds (1% CC and SG) might be attributed to higher yolk protein synthesis and an increase in water and mineral availability (Novak et al, 2004) and greater retention of feed in the gastrointestinal tract and thus a better ileal digestibility of the feed (Piray et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…However, a decrease in the relative abundance of Bacilli in the probiotic-fed groups compared to the control, which was observed in the developer and layer phases, may suggest a feedback of lessened potential pathogens after its supplementation (72,76), possibly creating a conducive environment in modifying the structure of the cecal microbiome. On the other hand, probiotics containing dead organisms have also been shown to express beneficial effects (77,78), such as by inducing specific immune responses based on the ability of immune cells to recognize individual bacterial cell structural components (79). These theories may suggest possible indirect attributes of the probiotic strain used in the present study, which were evidenced through the improved AR of most components, in the developer phase for the probiotic supplemented group, particularly with the LSSB and MSSB, despite a decreased relative abundance of Bacilli in the former dose of supplementation, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The body immune status improved by regulating the intestine mucosal cytokines (Patterson & Burkholder, ). However, some studies found that dietary probiotics in diets showed little beneficial effects on its immune status, and this might be due to the different experimental design and the different time of collection (Mountzouris et al, ; Zhang, Xie, et al, ). As for the serum antibody levels of laying breeders, we found that supplementation with B. subtilis C‐3102 improved AIV‐Ab level in a linear manner, and there were no differences for NDV‐Ab level among all groups.…”
Section: Discussionmentioning
confidence: 99%